ENSURING AND GUARANTEEING THE PETITION RIGHT IN ROMANIA AND THE REPUBLIC OF MOLDOVA - Cătălin-Radu PAVEL (Challenges of the Knowledge Society)
The aim of the present study is to analyze the ensuring and guaranteeing the petition right in Romania and Republic of Moldova as a consequence for ensuring of a good administration. The objectives of this study were to analyze the petition right as a fundamental guarantee and the correlation with ensuring of a good administration. In this research we have highlighted the importance of granting the petition right for the citizens and the contribution to the developing of a good administration of the state in the favor of the citizens.